2015
DOI: 10.1111/ijd.12943
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous mycoses in coastal Karnataka in south India

Abstract: Subcutaneous mycoses are a rare group of disorders. Chromoblastomycosis is the most frequent subcutaneous fungal infection in south India. Morphologically, chromomoblastomycoses present as verrucous, ulcerative, nodular, or eczematous lesions. Clinical diagnosis is important as culture is often negative. The incidence of infection is higher among rubber tappers. It is important to clinically differentiate chromoblastomycosis from tuberculosis verrucosa cutis. Most of the subcutaneous mycoses respond well to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…The most common occupation associated with deep mycoses in this study was agriculture (50%) in concordance with 52.8% reported by Yun et al 8 Bhat et al also observed agriculture to be the main occupation. 7 In this study, 63.4% of patients were from rural areas while 19.5% were from semi urban areas, similar to the observation by Bhat et al that subcutaneous mycoses were more prevalent in rural areas. 7 This is explained by the fact that subcutaneous mycoses result due to the inoculation of saprophytic fungi present in the soil, decaying vegetation and the rural population, especially the adult males are more exposed to such an environment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The most common occupation associated with deep mycoses in this study was agriculture (50%) in concordance with 52.8% reported by Yun et al 8 Bhat et al also observed agriculture to be the main occupation. 7 In this study, 63.4% of patients were from rural areas while 19.5% were from semi urban areas, similar to the observation by Bhat et al that subcutaneous mycoses were more prevalent in rural areas. 7 This is explained by the fact that subcutaneous mycoses result due to the inoculation of saprophytic fungi present in the soil, decaying vegetation and the rural population, especially the adult males are more exposed to such an environment.…”
Section: Discussionsupporting
confidence: 90%
“…7 In this study, 63.4% of patients were from rural areas while 19.5% were from semi urban areas, similar to the observation by Bhat et al that subcutaneous mycoses were more prevalent in rural areas. 7 This is explained by the fact that subcutaneous mycoses result due to the inoculation of saprophytic fungi present in the soil, decaying vegetation and the rural population, especially the adult males are more exposed to such an environment. 9 History of trauma was present in 48.8% of patients in this study, close to 41.2% reported by Yun et al 8 Most often, patients with subcutaneous mycoses which are characterised by long incubation periods, do not recall the trivial trauma.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is a broad group which includes the following species namely Fusarium, Penicillium, Scedosporium, Acremonium, Paecilomyces, Aspergillus etc [1]. In the study by Bhat et al [14] the mean age of patients with subcutaneous infection was 49.4 years and the youngest age was 14 years and was more prevalent in rural areas.…”
Section: Original Research Articlementioning
confidence: 99%